Potential neuroprotective effects of fermented foods and beverages in old age: a systematic review - Porras-García, Elena; Fernández-Espada Calderón, Irene; Gavala-González, Juan; Fernández-García, José Carlos (Frontiers in Nutrition, 2023)
Purpose: Numerous articles have recently studied the involvement of the gut microbiota in neurological diseases. Ageing is associated with changes in the microbiome, which implies a reduction in microbial biodiversity among other changes. Considering that the consumption of a fermented-food diet improves intestinal permeability and barrier function, it seems of interest to study its participation in the prevention of neurodegenerative diseases. This article reviews existing studies to establish whether the consumption of fermented foods and fermented beverages prevents or ameliorates neurodegenerative decline in old age. Methods: The protocol used was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Details of the protocol for this systematic review are registered on PROSPERO (CRD42021250921). Results: Out of 465 articles identified in the Pubmed, Scopus, and Cochrane Library databases, a total of 29 that examined the relationship of the consumption of fermented products with cognitive impairment in old people were selected (22 cohort, 4 case-control, and 3 cross-sectional studies). The results suggest that low-to-moderate alcohol consumption and daily intake of coffee, soy products, and fermented-food diets in general are associated with a lower risk of dementia and Alzheimer's disease. Conclusion: Daily consumption of fermented foods and beverages, either alone or as part of a diet, has neuroprotective effects and slows cognitive decline in old people